Light-Triggered Adhesive Silk-Based Film for Effective Photodynamic Antibacterial Therapy and Rapid Hemostasis - Huang, Tingting; Zhou, Zhihao; Li, Qiaoyuan; Tang, Xiaoxuan; Chen, Xiaoli; Ge, Yifan; Ling, Jue (Frontiers in Bioengineering and Biotechnology, 2022)
Successful control of massive hemorrhage in deep wounds with irregular shape and low elasticity still remains great challenges in clinic. As the wound sites are usually at risk of bacterial infection, it is necessary to design an ideal hemostatic agents with rapid hemostasis and excellent antibacterial activity. In this study, we developed a light responsive hemostatic film for effective handling liver bleeding with promising photodynamic therapy against S. aureus upon near infrared (NIR) irradiation. Based on silk fibroin, the film exhibited desirable biocompatibility and mechanical property as a hemostat tape. Significantly, the film tape achieved excellent tissue adhesion and hemostasis in vivo within 2 min of UV exposure, which would have a great potential as a multifunctional biomedical material in the field of tissue repair such as wound healing, bone repair and nerve regeneration.